2017
DOI: 10.4254/wjh.v9.i6.300
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, histology, and histogenesis of combined hepatocellular-cholangiocarcinoma

Abstract: Combined hepatocellular-cholangiocarcinoma (CHC) is a rare tumor with poor prognosis, with incidence ranging from 1.0%-4.7% of all primary hepatic tumors. This entity will be soon renamed as hepato-cholangiocarcinoma. The known risk factors for hepatocellular carcinoma (HCC) have been implicated for CHC including viral hepatitis and cirrhosis. It is difficult to diagnose this tumor pre-operatively. The predominant histologic component within the tumor largely determines the predominant radiographic features ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 58 publications
1
84
1
1
Order By: Relevance
“…Our results showed that the OS of patients with CHC was significantly poorer than that of patients with HCC but not significantly different from patients with ICC, while CHC was associated with a significantly poorer DFS than either HCC or ICC. Adverse clinicopathological prognostic factors associated with tumor recurrence and survival have been reported in several studies and included large tumor size (> 5 cm), presence of satellite nodules, lymph node involvement, multifocality, vascular invasion, portal vein invasion, high tumor stage, high levels of CA19‐9, decreased capsule formation, and free surgical margins < 2 cm . However, many of these factors were not significant according to multivariate analysis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our results showed that the OS of patients with CHC was significantly poorer than that of patients with HCC but not significantly different from patients with ICC, while CHC was associated with a significantly poorer DFS than either HCC or ICC. Adverse clinicopathological prognostic factors associated with tumor recurrence and survival have been reported in several studies and included large tumor size (> 5 cm), presence of satellite nodules, lymph node involvement, multifocality, vascular invasion, portal vein invasion, high tumor stage, high levels of CA19‐9, decreased capsule formation, and free surgical margins < 2 cm . However, many of these factors were not significant according to multivariate analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Combined hepatocellular–cholangiocarcinoma is difficult to diagnose preoperatively due to its heterogeneous imaging characteristics, with features that overlap both HCC and ICC . Thus, most CHC cases are initially misdiagnosed as either HCC or ICC, and the correct diagnosis is only reached after examination of surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, we preoperatively considered the diagnosis of cHC based on the combined radiological features of hepatocellular carcinoma and cholangiocarcinoma, together with raised levels of both tumor markers 4) ; however, the accurate diagnosis of this rare disease remains clinically difficult. In particular, sarcomatoid changes within cHC are rarer still and more reported cases are needed to establish diagnostic radiological features.…”
Section: Discussionmentioning
confidence: 99%
“…Studies which have evaluated the prevalence of these tumours suggest that they comprise between 2% and 5% of all primary liver malignancies,12 22–25 and interestingly, they have been reported to occur in both cirrhotic and non-cirrhotic livers 25–27. Of note, there is minimal evidence evaluating liver transplantation and the use of neoadjuvant therapy in these tumours; when these tumours are found in hepatic explants, it is typically incidental in nature or are from patients who were misdiagnosed as having traditional HCC 28. As discussed by Brunt et al , there is a need to study the outcome of these mixed tumours following hepatic transplantation as well as their response to various locoregional therapies and modern targeted treatments 21.…”
Section: Tumour Types Treated With Neoadjuvant Therapymentioning
confidence: 99%